APPLICATION OF ANTI-AVERSION TREATMENT FROM AYURVEDA IN SKIN CARE (VAIKRUTAPAHA CHIKITSA) - P.S, Arun Babu.; Shailaja, S.V.; Mishra, Baidyanath (International Journal of Ayurveda and Pharma Research, 2015)
Skin is the largest organ of the body. Healthy skin is a reflection of overall wellness. Acharya Sushruta advised certain procedures for the management of skin abnormalities under the heading of Vaikrutapaha chikitsa. These include procedures like Pandukarma (hypopigmentation), Krishnakarma (hyperpigmentation), Romasanjanana (repilation), Lomapaharana (depilation), Pratisarana (rubbing), Utsadana (stimulating granulation) and Avasadana (depressing granulation). Inclusion of such procedures light up the fact that cosmetology was given utmost importance even in the Vedic period. In modern day practice of Ayurveda, Vaikrutapaha chikitsa remains unnoticed in the shadow of surgical measures. These days people need faster results. So they usually opt for procedures that can result in faster relief like facial surgery, laser hair removal, hair transplants, chemical skin peels etc. These are usually costly and may be out of reach of common man. So there arises a need for a result oriented procedure which is natural, cost effective and devoid of side effects. Having said that Vaikrutapaha chikitsa comes into picture in this aspect. There is no doubt that if these procedures are properly adopted in practice, it could bring lot of positive approach among the needy. Every human desires to look beautiful. With the advancement in various ultratechnology, maintenance of beauty has been made easy. But there is equal demand for natural methods and principles in keeping skin, mind and body healthy to remain beautiful. In this circumstances Vaikrutapaha chikitsa stands unique.